Physicochemical properties changes on Malaysia’s biomass torrefaction and development of torrefaction correlation model - Nur Hazirah Huda, Mohd Harun (2019)
Nowadays, torrefaction has become one of the important pretreatment technologies to upgrade the properties of biomass in order to promote utilization of biomass for sustainable energy production. Torrefaction is a thermal process that occurs in an inert oxygen-free environment at temperature range of 200 – 300°C. Throughout the process, biomass is decomposed and some properties of biomass changed as a result of structure destruction. In general, torrefied biomass has darker color, high energy density, high heating value and exhibits hydrophobic characteristic that makes it easier for grinding. Therefore, the objectives of this research are to conduct an experimental work in order to identify the effect of torrefaction on the physicochemical properties of biomass and to development of linear correlation model and mathematical model for anhydrous weight loss (AWL) evaluation. Torrefaction experiments were conducted in a tubular reactor at four different temperatures (240, 270, 300 and 330°C), in an inert nitrogen condition at three different residence times (15, 30 and 60 minutes). The effect of torrefaction on three types of oil palm waste (empty fruit bunch, palm kernel shell, oil palm frond) and three types of forestry residue (meranti, kulim, cengal) samples were assessed by conducting several analyses following the standard procedure for fuel. Analyses performed were proximate analysis and ultimate analysis, calorific value analysis (HHV) and scanning electron miscroscopy (SEM). Based on the properties of torrefied oil palm waste and forestry residue, the correlation of the properties data were evaluated with respect to mass loss data for Linear Regression Model purpose. Concurrently, three kinetic models w ere analysed and developed to briefly demonstrate the real torrefaction process using oil palm waste and forestry residue samples. AWL model used were Simple Global Model, a two reaction in series model namely Di Blasi-Lanzetta model and three parallel reaction namely Rousset Model in which all kinetic parameters that represents the evolution of solid and volatile products are predicted and simulated using Matlab R2014a. Later, parameters obtained from the simulation work were fine-tuned in order to fit the predicted mass loss and volatiles distribution with the experimental data. From the results obtained, mass yield for oil palm waste and forestry residues were reduced about 20 to 40%. Energy yield for oil palm waste decreased for about 20% whereas energy yield for forestry residues increased for about the same. HHV for torrefied oil palm waste and forestry residue are in the range of 22 – 26 MJkg–1. These values are in the range of HHV for coal which is 24 – 35 MJkg–1. In conclusion, it is proven that torrefaction can improve the fuel characteristics of biomass based on the HHV value, proximate analysis and ultimate analysis. Among oil palm waste, palm kernel shell is the most suitable feedstock for torrefaction as recorded HHV is 25.83 MJkg–1@330°C whereas cengal is the most suitable feedstock for forestry residue (25.45 MJkg–1@330°C). Good regression value has been obtained indicating a reliable correlation model has been developed for predicting the proximate and ultimate analysis using mass loss as an input. For AWL modelling, Di Blasi-Lanzetta and Rousset Model have accurately demonstrated the AWL of the respective biomass. The models were validated with the experimental data therefore, can be implemented to predict the AWL of various biomass.